From a biomechanical perspective: pathogenesis, clinical manifestations and treatment strategies of adolescent idiopathic scoliosis - Li, Dongmei; Mo, Haokun; Yang, Siying (Frontiers in Pediatrics, 2025)
PurposeAdolescent Idiopathic Scoliosis (AIS) is a complex three-dimensional spinal deformity, and its etiology and progression mechanisms have not been fully elucidated. This review aims to comprehensively explain the pathogenesis, clinical manifestations, and treatment strategies of AIS from a biomechanical perspective, providing a new theoretical framework for clinical diagnosis and treatment.MethodsThis review strictly follows the PRISMA guidelines for systematic literature search and selection. The search databases include PubMed, Embase, Web of Science, and Cochrane Library, with the cutoff date being June 2025. The search strategy involves a combination of keywords related to AIS, biomechanics, pathogenesis, clinical manifestations, and treatment. By progressively screening titles, abstracts, and full-text articles, relevant high-quality studies were ultimately included for comprehensive analysis.ResultsThe pathogenesis of AIS can be conceptualized as a “vicious cycle” driven by the interactional imbalance between passive subsystems (skeletal-ligament), active subsystems (muscles), and neurocontrolled subsystems (central and peripheral nerves). Biomechanical factors play a key role in driving the progression from initial minor imbalances to significant three-dimensional deformities. Clinically, symptoms such as body deformity, back pain, and reduced cardiopulmonary function can all be directly interpreted from a biomechanical perspective. In terms of treatment, all mainstream interventions (including observation, specific exercise rehabilitation, bracing, and surgery) fundamentally rely on biomechanical correction.ConclusionThe biomechanical perspective provides an indispensable integrative framework for understanding AIS. It unifies the process from molecular abnormalities to macro deformities, linking the diverse clinical manifestations and treatment approaches. Further exploration of biomechanical mechanisms is of significant importance for optimizing treatment timing and improving long-term patient outcomes.